PENGARUH WORK-LIFE BALANCE, LINGKUNGAN KERJA FISIK, STRES KERJA TERHADAP KEPUASAN KERJA (STUDI KASUS PADA DIVISI PRODUKSI PT TELEVISI TRANSFORMASI INDONESIA) - Meizha Nabila Putri (2022)
This research is a quantitative research with the aim of knowing the effect of work-life balance, physical work environment, work stress on job satisfaction. The total population is 169 and the sample is 85 permanent employees in the production division of PT Television Transformation Indonesia. The analysis technique use quantitative data analysis using Partial Least Square (PLS). The result of this study indicate (1) work-life balance has a positive and significant effect on job satisfaction, (2) physical work environment has a positive and significant effect on job satisfaction, (3) work stress has a positive and significant effect on job satisfaction, and (4) work-life balance, physical work environment, work stress simultaneously have a positive effect on job satisfaction.